Atributos químicos e físicos do solo após a aplicação de doses de gesso agrícola e o rendimento do trigo e soja em sucessão - Bartzen, Bruna Thaina (2020)
Agricultural gypsum is a source of Ca and S and can bring improvements in the chemical attributes of the soil, with the potential to increase the productivity of wheat and soybean crops. In this sense, the objective of the present work was to evaluate the effect of doses of agricultural plaster on the physical attributes of the soil, nutrient contents (soil and plant), as well as the development of wheat and soybean crops in succession in the Direct Planting System (DPS). The experiment was implemented in August 2017, at Copagril Experimental Station, belonging to Copagril Agroindustrial Cooperative, in the municipality of Marechal Cândido Rondon - PR, in an Eutropheric Red Latosol. The experimental design used was randomized blocks, with treatments consisting of six doses of agricultural plaster (0, 600, 1200, 2400, 4800 and 9600 kg ha-1). In May 2018 the sowing of the wheat crop was carried out, in which, at the time of harvest, the yield components were evaluated (plant height, tillering, ear length, number of spikelets, number of grains per ear, mass of thousand grains and productivity). In addition, soil nutrient content and physical attributes (macro, microporosity, total porosity, density and resistance to soil penetration) were quantified, at a depth of 0-40 cm, after 18 months of plaster application. In September 2018, the soybean crop was implanted, and the effect of treatments on the yield components of the crop was evaluated. Leaf collection was performed to quantify the levels of macronutrients in wheat and soybean crops. The results obtained after 18 months of application of the plaster indicate that it did not influence the active acidity, as well as the K content of the soil. It caused an increase in the potential acidity of the soil up to the dose 2400 and 1200 kg ha-1 in the 0-10 and 20- 40 cm layer, respectively, and a reduction in the 10-20 cm layer up to the dose of 1200 kg ha-1. The 1200 kg ha-1 dose increased the Ca, Mg and base saturation levels in the 10-20 cm layer and the S content in the two deepest layers of the soil. CTCpH7.0 increased to a dose of 2400 kg ha-1. The 1200 kg ha-1 dose increased the levels of K and S in wheat and Mg and K in soybean. Regarding macroporosity (Ma), microporosity (Mi), total porosity (Pt) and density (Ds), the doses of 600 and 1200 kg ha-1 obtained the highest values of Ma, Mi and Pt. The lowest values of Ds in the evaluated layers (0 - 40 cm), improving the physical quality of the soil. The 1200 kg ha-1 dose obtained the lowest values for soil resistance to root penetration (RP) in the evaluated layers (0 - 40 cm). The use of agricultural gypsum did not favor the increase in productivity of wheat and soybean crops.